Istrien 1840-1914 Eine kulturelle Versuchsstation des Habsburgerreiches - Toncich, Francesco (Mohr Siebeck, 2021)
Between 1840 and 1914, the Istrian peninsula was identified as a cultural laboratory in order to explain the cultural diversity and hybridity within the Habsburg Empire. Francesco Toncich analyses the activities of the local and imperial researchers in developing new kinds of identifications through scientific knowledge.
PublicationDate: 20211109
Keywords: Istrien -- Habsburgermonarchie -- Ethnisierung -- Aufführungsrecht -- Kulturelle Reinheit vs. Hybridität -- Adria -- Corpus Pastorale -- Sozial-/Kulturwissenschaften -- 19.-21. Jahrhundert -- Wissenschaftsgeschichte